Back to nature a historical study of Batangas-based community newspaper Pahayagang Balikas - Estabas, Charmaine C.
This study aimed to trace the history and development of Pahayagang Balikas, a community newspaper based in Batangas that emphasizes environmental issues. Guided by the Political Economy of Mass Media and the Agenda Setting Theory, the study interviewed key figures, including the founder and former editorial staff, and conducted archival research to explore the origin and growth of Pahayagang Balikas. A sample of 59 issues released between 2019 and 2023 was also analyzed to assess the newspaper's environmental coverage. The findings showed that Pahayagang Balikas was first published in March 1996 to promote environmental awareness amid the construction of a power plant in Mauban, Quezon. Institutional support and changes in ownership enabled its survival amid challenges in funding, staffing, and advertising. Over the years, the newspaper continued to prioritize environmental issues while also publishing other community-relevant stories; however, the content analysis revealed a growing trend in business coverage.